Analisis Kualitas dan Kuantitas Air Limbah Domestik di Institut Teknologi Kalimantan (Studi Kasus: Gedung B) - Chandra Suryani Rahendaputri; Reza Mahendra; Ryan Dwi Prakoso; Wanda Dwi Anggraini; Muhammad Airy Ichlasul Rana; Budiani F. Endrawati (SPECTA Journal of Technology, 2022)
Disposal of wastewater originating from domestic and industrial activities into water bodies can cause environmental pollution if the quality of the wastewater does not meet wastewater quality standard. Kalimantan Institute of Technology (ITK), is a campus that supports the ¬eco-campus program. One of the eco-campus criteria is wastewater treatment. Therefore, in this study the amount of greywater wastewater from the sink of Building B ITK and the quantity of pH, TSS and phosphate parameters will be studied using the sampling method and sampling test according to SNI, to then formulate the treatment. In the preliminary research it was found that the pH level was 7.04 when tested immediately, and decreased to 5.81 when the sample was left for two days. The TSS level was 0 mg/L and the phosphate level was in the 0,080 mg/L to 0,0807 mg/L. All three parameters are still below the quality standard. Therefore, the greywater from the sink waste in Building B ITK can be processed to be utilized directly without treatment but not for potable.